PERFORMANCE OF DURABILITY CHARACTERISTICS ON HIGH STRENGTH CONCRETE USING NANO CLAY, RED MUD AND SILICA FUME ADMIXTURES - Khazalah, Dr.Mahmoud Al; Rajesh, A.Maria; Joe, M.Adams (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
The paper deals with the performance of durability characteristics using Nano clay,red mud and silica fume to produce a high strength concrete. This study is mainly concentratedon the durability characteristics of HSC with some percentage replacement of cement by redmud, nano clay and silica fume. The cement was replaced with 75% to 60% at 2.5% interval bymineral admixture such as red mud, nano clay and silica fume. Water cement ratio is keptconstant for all mixtures. The main aim of paper is to be found out the acid and chloride resistingcapacity of the specimens. The result shows that the combination of third sample produced 20%more resisting capacity of acid and chloride immersion compared with other samples from theexperimental.